Perancangan Aplikasi Mobile Secure Lab Pada Ruangan Laboratorium Telekomunikasi Politeknik Negeri Jakarta - Viving Frendiana; Afif Tadjuddin Shaf (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2023)
The Telecommunications Engineering Laboratory is one of the laboratories under the Department of Electrical Engineering, at Jakarta State Polytechnic. To increase the security of the laboratory room, a mobile application called Secure Lab can be used, where a door lock with a QR code is connected to the application. The QR code functions as a room key which was built using Android Studio and uses the Kotlin programming language. This application is also connected to Authentication and Realtime Database on Firebase. There are two access rights to the Secure Lab application, namely as a lecturer and a student. To act as a student, you need to create an account first so you can request room access using a QR code and open the door. Acting as a lecturer has the right to provide QR code access to students, which can be used to open the room door within a predetermined period. Secure Lab application testing is intended to determine the application's feasibility. From three tests: Compatibility, Functional Suitability, and Portability aspects, very decent results were obtained. From the QR code reading test, the result was that a scanner could read the QR code produced by the Secure Lab application. Testing based on the distance obtained results that 10-16 cm is the distance that can still be read by the scanner.